The parent function is:
y = x ^ 2
Applying the following function transformation we have:
Horizontal translations:
Suppose that h> 0
To graph y = f (x-h), move the graph of h units to the right.
We have then:
g (x) = (x-2) ^ 2
Then, we have the following function transformation:
Vertical translations
Suppose that k> 0
To graph y = f (x) + k, move the graph of k units up.
We have then that the original function is:
g (x) = (x-2) ^ 2
Applying the transformation we have
f (x) = g (x) +3
f (x) = (x-2) ^ 2 + 3
Answer:
the function f(x) moves horizontally 2 units rigth.
The function f (x) is shifted vertically 3 units up.
Step-by-step explanation:
x = the number
2x - 25 = x
2x = x + 25
x = 25
Answer:
80%
Step-by-step explanation:
If you divide 52 by 65 you will get a decimal, then multiply by 100% to get the equivalent.
52/65 = 0.8
0.8 x 100 = 80%
Answer:
C f=9
Step-by-step explanation:
isolate f on one side so you subtract 5 from both sides to get 3f=27 and then divide by 3 on each side to get f=9